2003
DOI: 10.1002/elps.200390151
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a resistive region at the anode end in DNA capillary electrophoresis

Abstract: We have studied the formation of a resistive region in the capillary during DNA separation. This effect is caused by an unequal change in the mobilities of cations and anions at the interface between the running buffer solution and the capillary. We studied the motion of the resistive region boundary by sequential removal of portions of the affected capillary end. We found that in the process of developing the resistive region the distribution of the electric fields in the capillary changes from uniform to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…These effects are particularly pronounced in the sample well and most dominantly associated with spatially and temporally varying fields near the matrix/water interface. Similar effects have been observed for a long time in capillary devices [17]. However, because of the timing-critical voltage switching aspect of crossinjectors, they have much more pronounced effects on the performance of microdevices than was previously observed in capillaries.…”
Section: Discussionmentioning
confidence: 70%
“…These effects are particularly pronounced in the sample well and most dominantly associated with spatially and temporally varying fields near the matrix/water interface. Similar effects have been observed for a long time in capillary devices [17]. However, because of the timing-critical voltage switching aspect of crossinjectors, they have much more pronounced effects on the performance of microdevices than was previously observed in capillaries.…”
Section: Discussionmentioning
confidence: 70%
“…Ion distribution was measured by the cut capillary method [12,14]. This required removing the capillary from the apparatus, which cooled it from 557C to 207C, causing the matrix to shrink about 5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The Swerdlow group [3] also studied the effect of DNA samples, and explicitly showed that rapid current decline was associated with the injection of a sufficient quantity of fragments longer than 1300 bp, and that smaller quantities did not cause the effect to occur. While sample-independent current decline has been minimized in commercial instruments through judicious selection of buffer and matrix components [13,14], the swift and severe current decline from large fragments continues to be a concern.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to all the above-quoted papers describing formation of the resistive region at the cathode end of the capillary, we consistently observed the resistive region at the anode (detection) end. This gave us an opportunity to directly study the behavior of the DNA peaks in this region [13].…”
Section: Introductionmentioning
confidence: 99%
“…In [13], for characterization of the migration of high-resistivity zones, we measured time-dependent electric current, and then determined the length of the influenced region by a sequential removal of small (1 mm) pieces of the affected capillary end. This method suffered from two major shortcomings: first, the accuracy of the measured length of the resistive region was rather low and second, the measurement destroyed the capillary and was difficult to reproduce.…”
Section: Introductionmentioning
confidence: 99%